2011
DOI: 10.1038/onc.2011.50
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of thyroid hormone receptor-β in mice predisposes to the development of mammary tumors

Abstract: Correlative data suggest that thyroid hormone receptor-β (TRβ) mutations could increase the risk of mammary tumor development, but unequivocal evidence is still lacking. To explore the role of TRβ mutants in vivo in breast tumor development and progression, we took advantage of a knock-in mouse model harboring a mutation in the Thrb gene encoding TRβ (ThrbPV mouse). Although in adult nulliparous females, a single ThrbPV allele did not contribute to mammary gland abnormalities, the presence of two ThrbPV allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 66 publications
2
31
0
Order By: Relevance
“…Mammary glands with alveolarization could be due to the increased P 4 levels, as P 4 is known to cause alveolarization and milk production (Conneely et al 2003). A previous study also observed increased mammary gland alveolarization in heterozygous PTENKO females, but P 4 levels were not determined (Guigon et al 2011). We also showed that less PTENARKO females appeared to have alveolarized mammary glands compared to PTENKO, further supporting the reduced P 4 levels in PTENARKO compared to PTENKO females.…”
Section: Discussionsupporting
confidence: 72%
“…Mammary glands with alveolarization could be due to the increased P 4 levels, as P 4 is known to cause alveolarization and milk production (Conneely et al 2003). A previous study also observed increased mammary gland alveolarization in heterozygous PTENKO females, but P 4 levels were not determined (Guigon et al 2011). We also showed that less PTENARKO females appeared to have alveolarized mammary glands compared to PTENKO, further supporting the reduced P 4 levels in PTENARKO compared to PTENKO females.…”
Section: Discussionsupporting
confidence: 72%
“…THRB can act as a transcriptional activator or silencer depending on the presence or absence of its ligand, thyroid hormone triiodothyronine. In addition, Guigon et al [21] demonstrated that TRβ mutation promotes the development of mammary hyperplasia via aberrant activation of the signal transducer and activator of transcription 5A (STAT5) pathway. Alterations in TR expression also were observed in a subset of patients with breast cancer [22].…”
Section: Discussionmentioning
confidence: 98%
“…Functional loss or modifications of these transcription factors are increasingly recognized in human cancers. Dysregulation of TRs through point and frameshift mutations as well as epigenetic silencing is established in a variety of solid tumors (31)(32)(33)(34)(35)(36)(37)(38)(39)(40). The propensity for reduced expression of TRs, notably TR␤1, as tumorigenesis progresses is consonant with a suppressor role for TR (41)(42)(43).…”
mentioning
confidence: 94%